2009
DOI: 10.1007/s11695-009-9929-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Gastric Bypass in Patients 60 Years and Older: Early Postoperative Morbidity and Resolution of Comorbidities

Abstract: LGBRY can be done safely in patients over 60 years of age in an experienced bariatric program, even in patients with relatively high risk based on their comorbid conditions preoperatively. Resolution of associated comorbidities far exceeds that found with any other treatment modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Bariatric surgery has during recent years shown to be safe for patients over 60 years and older with good results especially considering resolving of comorbidities [1][2][3][4][5]. The recovery after the operation has been comparable with younger patients in these studies.…”
Section: Introductionmentioning
confidence: 70%
“…Bariatric surgery has during recent years shown to be safe for patients over 60 years and older with good results especially considering resolving of comorbidities [1][2][3][4][5]. The recovery after the operation has been comparable with younger patients in these studies.…”
Section: Introductionmentioning
confidence: 70%
“…However, the role of bariatric surgery in patients C60 years old is unclear regarding safety and efficacy [5][6][7][8][9][10] and was the purpose of our study. With the rising incidence of this agegroup combined with the epidemic of obesity, the rate of bariatric operations in patients C60 is increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, numerous authors have published studies on the safety and efficacy of bariatric operations in this patient population [2,[6][7][8][9][10].…”
mentioning
confidence: 99%
“…14 Single institution studies have been variable in their conclusions regarding perioperative safety of the elderly following bariatric surgery. [15][16][17][18][19] The utility of bariatric surgery in the elderly population is often queried. While this is beyond the scope of this paper, previous studies have demonstrated significant excess weight loss, improvement in quality of life, reduction in daily medication use, and improvement in obesity-related comorbid illness in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…While this is beyond the scope of this paper, previous studies have demonstrated significant excess weight loss, improvement in quality of life, reduction in daily medication use, and improvement in obesity-related comorbid illness in the elderly population. 15,16,18,19 Therefore, elderly patients do experience the benefits of bariatric surgery with acceptable rates of morbidity and mortality, and age alone should not function as an absolute deterrent. While this study contributes to the current knowledge of bariatric surgery, several limitations exist.…”
Section: Discussionmentioning
confidence: 99%